PENGARUH EMPLOYEE WORKLOAD DAN EMPLOYEE WORK STRESS TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI PT PGAS SOLUTION AREA PALEMBANG - Adi Martono; Zunaidah; Yos Karimudin (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of workload and work stress on employee performance through job satisfaction at PT PGAS Solution Area Palembang. Using a quantitative survey, data collected from 152 employees selected through proportionate stratified random sampling and analyzed using PLS-SEM with SmartPLS 4. Workload positively and significantly affected performance and job satisfaction, whereas work stress had no significant effect on either variable. Job satisfaction positively affected performance and significantly mediated the workload performance relationship but did not mediate the stress performance relationship. These findings emphasize proportional workload management and strengthen job satisfaction to sustain employee performance in high-risk energy operations. Keywords: Employee Workload; Employee Work Stress; Job Satisfaction; Employee Performance; SEM-PLS